Criteria and factors for the choice of private label brands by customers of retail chains - Muszyńska, Karolina (Kryteria i czynniki wyboru marek własnych sieci handlowych przez konsumentów, 2019)
The primary aim of the paper to determine the criteria and factors applied by customers making decisions about buying private label brands of retail chains. An additional goal is to examine their level of awareness regarding the place of origin and ingredients used in the production of own branded products. The development of private label brands and their functioning on the consumer goods market are discussed. An analysis of the image of private label brands in the eyes of customers was conducted. The research method used is a diagnostic survey carried out via the internet. The adopted research methodology allowed to answer all the questions posed. A review of empirical research results showed that factors influencing purchasing decisions differ between generations and that young people more often use products of private brands, especially groceries, than older people. The article is of a research nature
Management Sciences = Nauki o Zarządzaniu, 2019, vol. 24, no. 4, s. 18-23
Keywords: own brands; retail chains; consumer choices; marki własne; sieci handlowe; wybory konsumenckie